The impact of e-commerce drivers on e-customer loyalty: Evidence from KSA - Sura Al-Ayed (Growing Science, 2022)
E-commerce and online shopping is the future of global trade, hence the importance of building E-customer loyalty and maintaining it in the electronic markets becomes even more important. This paper attempts to identify factors affecting the value of electronic commerce in the Saudi environment. Likewise, it explores the impact of these factors on E- customer loyalty. Simple random sampling was used for the purposes of the current study, as the first study included 247 electronic customers. Data were collected through electronic questionnaires sent to the study participants. The results show that the factors had a positive impact in building E- customer loyalty Care, Character, Choice, Convenience, Customization, and Cultivation. Basically, e-commerce is considered a pioneer in business organizations today, and this is witnessed by its increasing and growing profits and expanding its market share, through its focus on the E-loyalty customers. Basically, e-commerce is considered a pioneer in business organizations today, and this is witnessed by its increasing and growing profits and expanding its market share, through its focus on the E-loyalty customers.